The Commonwealth Bank of Australia – Strategizing from Outsourcing to the Cloud Part 1: Perennial Challenges Amidst Turbulent Technology. Issue 2 (January 2015) - Willcocks, Leslie; Reynolds, Peter
This teaching case examines the challenges of using Information Technology (IT) outsourcing, adopting new technologies, undertaking business transformation, and evolving the IT function's structure, governance arrangements and capabilities – all in a dynamic business context. The Commonwealth Bank Australia has over the last 20 years experienced similar IT management dilemmas as countless organizations across the globe. The case foregrounds six perennial issues in IT management. First, what form of outsourcing is suitable at different stages of an organization's development, and how can that outsourcing be managed? The case here covers the challenges of single and multi-supplier outsourcing. Part 2 will focus on sourcing issues with cloud computing. Second, what are the key IT capabilities that must be retained within a large corporation? Part 2 will ask whether these capabilities change with cloud computing. Third, what are the mechanisms for developing, nurturing, maintaining, and evolving retained capabilities? Fourth, how should IT be governed in the face of changing business needs, new technologies, and changing organization structures? Fifth, Parts 1 and 2 of the case question the roles of the CEO, CIO, and business managers in leveraging IT performance for business value, the building of project and program management capabilities, and how to organize IT to support a business transformation program. Finally, the case raises the challenge for students of how an organization with its history and legacy in technology and sourcing partners can then move into even newer technologies – in this scenario cloud computing – the primary focus of Part 2 of the case. Overall, the two cases raise the fundamental challenge – what perennial management practices are effective, over time, in dealing with the challenges raised by changing technologies, and what new practices may be required, in contemporary dynamic business contexts.